Aktivitas Public Relations Santasea Waterpark di Media Sosial (@santaseawaterpark) - Ahmad Agus Salim; Kurnia Handita (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to analyze the public relations activities conducted by SantaSea Waterpark through Instagram in enhancing public brand awareness. The research employs a descriptive qualitative approach using a case study method. Data were obtained through observation of the Instagram account @santaseawaterpark and literature review related to digital public relations. The findings indicate that the public relations activities include information dissemination, promotions, special events, and audience engagement. These efforts effectively foster user engagement and contribute to increasing SantaSea Waterpark's brand awareness. Positive responses from Instagram followers and users towards promotional and event-related content serve as indicators of the effectiveness of the communication strategies employed.